How the Arabian nights inspired the American dream, 1790-1935 - Nance, Susan (University of North Carolina Press, 2009)
Americans have always shown a fascination with the people, customs, and legends of the "East"--Witness the popularity of the stories of the Arabian Nights, the performances of Arab belly dancers and acrobats, the feats of turban-wearing vaudeville magicians, and even the antics of fez-topped Shriners. In this captivating volume, Susan Nance provides a social and cultural history of this highly popular genre of Easternized performance in America until the Great Depression. According to Nance, these traditions reveal how a broad spectrum of Americans, including recent immigrants and im